2022
DOI: 10.1136/jitc-2022-004725
|View full text |Cite
|
Sign up to set email alerts
|

TEM8 Tri-specific Killer Engager binds both tumor and tumor stroma to specifically engage natural killer cell anti-tumor activity

Abstract: BackgroundThe tumor microenvironment contains stromal cells, including endothelial cells and fibroblasts, that aid tumor growth and impair immune cell function. Many solid tumors remain difficult to cure because of tumor-promoting stromal cells, but current therapies targeting tumor stromal cells are constrained by modest efficacy and toxicities. TEM8 is a surface antigen selectively upregulated on tumor and tumor stromal cells, endothelial cells and fibroblasts that may be targeted with specific natural kille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Although most NKCEs are currently in the preclinical stage and their safety and efficacy need further evaluation, it is undeniable that they are emerging as highly promising tumour therapeutic strategies and have the potential to overcome the suppressive TME due to their target specificity [ 235 ]. It has been observed that 161,533 TriKE exhibits excellent antitumour activity and promotes NK cell persistence in vivo [ 236 ].…”
Section: Current Therapeutic Strategies For Overcoming the Tmementioning
confidence: 99%
“…Although most NKCEs are currently in the preclinical stage and their safety and efficacy need further evaluation, it is undeniable that they are emerging as highly promising tumour therapeutic strategies and have the potential to overcome the suppressive TME due to their target specificity [ 235 ]. It has been observed that 161,533 TriKE exhibits excellent antitumour activity and promotes NK cell persistence in vivo [ 236 ].…”
Section: Current Therapeutic Strategies For Overcoming the Tmementioning
confidence: 99%
“…Circulating NK cells would have to migrate from the periphery in order to kill tumor cells. The IL-15 component in TriKEs enhances NK cell mobility in vitro (53) and a TriKE targeting the tumor stroma was able to enhance NK cell infiltration into the tumor in an animal model (57). We would predict, therefore, that the IL-15 component of this TriKE, which targets lung cancer, would also enhance infiltration of NK cells directly into the tumor, but this remains to be shown.…”
Section: Discussionmentioning
confidence: 99%
“…The last domain of TriKE is antigen-specific which takes a role in specifically target the cancer cells to complete their bridge function which connects enhanced NK cells to the targeted cancer cells. Previously, various types of specificity were designed, such as anti-CD33 AML [ 7 , 25 ], anti-EpCAM against carcinomas [ 13 ], anti-CD19 against B-CLL [ 15 ] anti-TEM8 and anti-mesothelin against NSCLC [ 10 , 27 ], anti-CLEC12A against AML [ 9 ], and anti-HER2 against ovarian cancer [ 26 ]. However, there are some interesting target antigens those have been used as potential target immunotherapy in other platforms, like monoclonal antibody (mAb), CAR-T cell, and other immune cell-engager: T cell engager and macrophage engager which can be applied to TriKEs construction [ 47 ].…”
Section: Trikementioning
confidence: 99%